Perilaku Belajar Anak Tunggal Ditinjau dari Perspektif Psikologi dan Sosiologi: Studi Kasus di SD Laboratorium UM - - Ruminiati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this research is to describe learning behavior of single child in the school, home, and community environment based on the sociology and psychology perspective. This research used descriptive qualitative research approach. The subjects were male and female elementary school students. This research found that single children tended to less independent, less confident in learning, less social, and more discipline.